STRATEGI PENGELOLAAN PERSEDIAAN BENANG JAHIT 60/20 DI PT X: MENGGUNAKAN PERAMALAN DOUBLE MOVING AVERAGE DAN ALGORITMA WAGNER WITHIN UNTUK OPTIMALISASI BIAYA - Cryselia Maysandi Limbong, Melinda; Isroqi, Vian; Iqbal Ramdani, Muhammad; Fauzi, Muchammad (Kohesi: Jurnal Sains dan Teknologi, 2025)
Problems in inventory management often lead to wasteful costs or stock shortages that can disrupt the company's operational efficiency. PT X faces the challenge of managing fluctuating demand for 60/20 sewing thread, the company's main product, effectively and efficiently. This study aims to overcome this problem by applying the Double Moving Average (DMA) method for demand forecasting and the Wagner Within algorithm for inventory cost optimization. The DMA forecasting results show high accuracy in predicting demand patterns, while the Wagner Within algorithm successfully minimizes total inventory costs by Rp9,780,600 during the January-December 2024 period. The combination of these two methods proves its effectiveness in supporting strategic inventory management decisions at PT X.